THE ROLE OF ZISWAF’S IN RESTRUKTURING INDONESIA ECONOMY IN COVID-19 ERA - Muhammad Luqman Hakim; Pria Mitra; Farras Nabila; Ahmad Al-Badawi; Maya Panorama (Berajah Journal, 2022)
Zakat, Infaq, Shodaqoh, and Waqf (ZISWAF) have great potential in Indonesia, especially the majority of Indonesian religious people according to the Ministry of Home Affairs (June 2021), amounting to 86.88% which is 236.53 million compared to 272.23 million. Based on the history when Umar Bin Abdul Aziz used ZISWAF, it was proven that ZISWAF was able to finance a country and its entire community. This research aims to provide solutions and the role of ZISWAF as one of the instruments of Sharia economy in dealing with the covid-19 pandemic. In this study, researchers used the Library Research approach method. From the data that has been mentioned that Indonesia will also advance not only on economic development and even able to make the people prosperous if ZISWAF is developed.